Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina) - Kamiński, Marcin J.; Schoeman, Colin S. (Zootaxa, 2018)
The genus Anaxius Fåhraeus, 1870 (Tenebrionidae: Helopinina) is revised to include seven Southern African species, four of which are new. A taxonomic treatment of the genus is provided including a morphological study, new species descriptions, keys, illustrations, and notes on species distributions. The following species are treated: Anaxius bloubergensis sp. nov., A. campbellae Koch, 1958, A. limpopoensis sp. nov., A. meletsensis sp. nov., A. obesus Fåhraeus, 1870, A. prozeskyi Koch, 1958, and A. pseudoloensus sp. nov. A lectotype is designated for Anaxius obesus Fåhraeus, 1870 to fix the taxonomic status of this species. Anaxius montiscaerulei Koch, 1958 is considered as a synonym of A. campbellae.